Level of Detail Parent and Dynamic Culling Scheme for Flight Simulator - Lee, Chung-Jae; Kim, Kyong-Hoon; Kim, Ki-Il (International Journal of Engineering and Technology, 2018)
Background/Objectives: Due to huge volume of data, it is required to reduce the number of vertices in flight simulator through level of detail and culling. However, it is required to integrate them accordingly.Methods/Statistical analysis: Due to high point of view, terrain data in wide area are usually rendered in the flight simulator. So, conservational level of detail and culling schemes have adaptation problem in flight simulator. To defeat this problem, dynamic culling scheme and level of detail parent method based on line of sight are proposed.Findings: Experiment scenarios are built to measure and compare the frame per second and number of vertices in four separate schemes, that is, scheme without the proposed algorithm, applying view frustum culling and applying culling and level of detail together and graphic processing unit based parallel processing algorithm, respectively. The proposed scheme reveals the similar values in the case of small-volume of terrain data. On the other hand, frame per second is significantly improved in huge volume of terrain data by reducing the number of vertices through dynamic culling and level of detail parent method. Specially, when level of detail parent method is applied to rendering the city with large number of buildings, the proposed scheme reveals the best frame per second among the comparative schemes.Improvements/Applications: Improved rendering algorithm was proposed to handle huge volume of terrain data and thereby to prove the applicability of the proposed scheme in other simulator.Â Â